Cardiac Drug Development Guide - Pugsley, Michael K;Ed (Methods in pharmacology and toxicology., 2003)
The revolution in molecular medicine makes it imperative to integrate the classical and molecular approaches to drug development for the treatment of heart disease, the number one killer in North America and Europe. In the Cardiac Drug Development Guide, basic medical researchers, clinicians, and pharmacologists join forces to comprehensively survey the most recent breakthroughs in molecular cardiology and review the latest drug discoveries in cardiac and cardiovascular medicine. Topics range from novel molecular targets for cardiac drug development, to functional endpoints for evaluating cardiac drug activity, to clinical aspects of cardiovascular therapeutics. The authors describe the most advanced procedures in cardiovascular pharmacology, including in vivo and in vitro whole animal studies, the electrophysiological methods used to study pacemaker cells, and the application of biochemical principles and technologies to novel therapeutic agents. Also discussed are the methods used to express the ion channels involved in cardiovascular pharmacology, adenoviral vector delivery for cardiovascular gene therapy, pharmacometrics in cardiovascular drug development, gender differences in heart failure, and angiogenesis therapies for coronary heart disease. Each chapter concisely illustrates the concepts described and includes comprehensive background information, detailed figures and tables, and an up-to-date list of the most important references. Comprehensive and easy-to-understand, the Cardiac Drug Development Guide offers pharmacologists, cardiologists, and physiologists not only a gold-standard survey of the many different methods being used to develop new heart drugs, but also details powerful new ways in which cardiovascular disease is targeted, from the whole organ to the genetic level.